Functional Performance as a Predictor of Injurious Falls in Older Adults. Issue 2 (February 2015) - Ward, Rachel E.; Leveille, Suzanne G.; Beauchamp, Marla K.; Travison, Thomas; Alexander, Neil; Jette, Alan M.; Bean, Jonathan F.
<x xml:space="preserve">Abstract</x> Objectives To determine whether a performance battery and its components aid in predicting injurious falls. Design Longitudinal analysis; prospective cohort study. Setting Clinical site. Participants Boston‐area community‐dwelling adults (N = 755; mean age ± SD 78.1 ± 5.4, 64.1% female, 77.6% white). Measurements Baseline functional performance was determined according to the Short Physical Performance Battery (SPPB), measuring balance, gait speed, and five repeated chair stands. Fall history (past year) and efficacy in performing 10 daily activities without falling were assessed. Falls were assessed using a daily calendar over 4 years. Injurious falls were defined as resulting in fractures, sprains, dislocations, pulled or torn muscles, ligaments, or tendons or seeking medical attention. Results Poorest chair stand performance (≥16.7 seconds) was associated with greater hazard of injurious falls than in all other chair stand performance groups (hazard ratio (HR) = 1.96, 95% confidence interval (CI) = 1.18–3.26 for ≥ 16.7 vs. 13.7–16.6 seconds; HR = 1.65, 95% CI = 1.07–2.55 for ≥ 16.7 vs. 11.2–13.6 seconds, HR = 1.60, 95% CI = 1.03–2.48 for ≥ 16.7 vs. <11.2 seconds). SPPB did not predict injurious falls. Fall history predicted injurious falls (HR = 1.82, 95% CI = 1.39–2.39); falls efficacy did not. Fall history and a slow chair stand (<16.7 seconds) had a 2‐year cumulative incidence rate of an injurious fall of 46% (95% CI = 0.34–0.58), nearly the combined rate of a positive fall history (0.29, 95% CI = 0.25–0.34) and a slow chair stand alone (0.21, 95% CI = 0.13–0.30). Conclusion An easily administered chair stand test may be sufficient for evaluating performance as part of a risk stratification strategy for injurious falls.